Cost Savings as a Result of Bortezomib Vial Sharing in Albania - Rustemi, Florjana; Malaj, Ledjan; Hoti, Ela; Balla, Enida (European Scientific Journal, ESJ, 2018)
The costs associated with current and emerging therapies, as well as supportive care, are significant and pose a tremendous financial burden to both patients and healthcare system. The objective of this study was to calculate the cost savings as a result of bortezomib vial sharing in the University Hospital Center â€œMother Teresaâ€ Tirana. This study was a retrospective analysis of the use of bortezomib in patients with multiple myeloma, using vial sharing technique to minimize wastage. The study has been conducted during the period January 1, 2015 to June 30, 2015 before vial sharing and January 1, 2016 to June 30, 2016 after vial sharing, thereby enabling us to share vial contents between patients. We compared the cost in euro for the treatment with bortezomib in order to determine the cost savings of vial sharing and cost-efficacy of individualised preparation. As a result, the cost savings for one cycle/patient using vial sharing was calculated 226.81 euro, a reduction of 25.96% compared to the period when we did not use vial sharing. During January 1, 2015 to June 30, 2015 the average treatment cost was calculated 873.36 euro/cycle/patient, compared with January 1, 2016 to June 30, 2016 when it was calculated 646.55 euro/cycle/patient. Due to cost savings of each treatment cycle we administered 62 individualised preparations of bortezomib more during January 1, 2016 to June 30, 2016 for the same budget allocated. The same approach should be adopted for other suitable drugs prepared in the University Hospital Center â€œMother Teresaâ€ Tirana.